CORPORATE INCOME TAX OF SMALL MEDIUM ENTERPRISE (SME) - Nurdayadi, Nurdayadi (Academic Research Centre Services, 2017)
Tax is recently getting the most important income source for the country. In the case of Indonesia, every year the government has increased the annual target of tax income, but it has not been easily and successfully to achieve. In 2013 the government wishes to target the sources of income tax deriving from that small and medium business scale. The research which focuses on the medium scale of corporate tax payer business, would like to see and evaluate implementation of Government Regulation number 46, year 2013 (PP 46/2013), by doing simulation and regression analysis. Those corporate tax payers with the annual sales of around Rp. 7,000,000,000,- seems to be facing a dilemma situation to whether or not to comply with. Particularly since this government regulation does not take into consideration the impact to the tax payers cash flow when financial trouble is being faced and even at the time the companies run in loss situation. It seems it has been the time for the government to review the effectiveness of this regulation, how is being implemented across the country, especially by those corporate tax payers who are preparing book keeping and submitting tax report. The issue of accuracy, accountability and financial engineering follows the implementation of creativity accounting and tax accounting treatment, should have been the concern of the tax office. The idea and advices of mandatory audited financial report is prominent in this research, in order to reach the more targeted collecting tax fund from this class of enterprises in Indonesia.